Supporting German occupiers: the pro-Vichy stance of the Basque newspaper ‘Eskualduna’ (Communication & Society, 2018)
Eskualduna, a weekly newspaper edited in Bayonne and the oldest and most influential Basque language media publication of the time, was shut down in 1944 by the new post-liberation French authorities because of its pro-Vichy and pro-German stance, while its editor, the priest Sauveur Aroçarena, was arrested and convicted. This article examines the basis of the accusation under which Eskualduna was seized, i.e. to what extent its editorial approach favored the Vichy regime led by Marshall Pétain and the German occupation. For this purpose, a sample of 32 editorial articles signed by Aroçarena after four landmarks of the war (declaration of war in 1939, first German occupation in 1940, occupation of Vichy France in 1942 and Normandy landings in 1944) has been analyzed following source analysis methodology. The analysis of Eskualduna’s editorials has been contextualized within the reality of the Basque society’s attitude towards German occupation in order to understand that Eskualduna’s position was in harmony with its community’s way of experiencing the war, the regime and the occupation. This research confirms that Eskualduna had overall a pro-Vichy stance, and points out that this approach was framed within a discourse of French patriotism, defense of Catholicism, personality cult and affirmation of Basque identity.